Two tales of the natural rate of interest - Lauri Vilmi (Bank of Finland, 2017)
We estimate the long-term natural rate of interest for the euro area with two specifications of a simple semi-structural macroeconomic model. The estimates provide competing interpretations for the euro area's current economic environment of weak growth, subdued inflation and exceptionally low nominal interest rates. In our first estimation, the current state of economy is attributed to persistent, recurring negative shocks to the output gap that restrain growth even when expansionary monetary policies are applied. The second estimation suggests that a large drop in the natural rate of interest is the problem, because, even with interest rates held close to zero, policy actions have not been able to revive the economy after major shocks in 2008, 2012 and 2016. As both views may explain some of the observed trends, the task of teasing out the drivers of current conditions and future trends is non-trivial. Nevertheless, policymakers should pay attention to both stories as they have quite different endings.
URN:NBN:fi:bof-201703081180
Keywords: C32; E43; E52; O40; 330; euro area monetary policy; natural rate of interest